Silencing of GhSHP1 hindered flowering and boll cracking in upland cotton - Xu, Wenjuan; Ma, Qi; Ju, Jisheng; Zhang, Xueli; Yuan, Wenmin; Hai, Han; Wang, Caixiang; Wang, Gang; Su, Junji (Frontiers in Plant Science, 2025)
The opening of cotton bolls is an important characteristic that influences the precocity of cotton. In the field, farmers often use chemical defoliants to induce cotton leaves to fall off earlier, thus accelerating the cracking of cotton bolls. However, the molecular mechanism of cotton boll cracking remains unclear. We identified ten AGAMOUS subfamily genes in upland cotton. Three pairs of Gossypium hirsutum AG subfamily genes (GhAGs) were amplified via tandem duplication. The promoters of the GhAGs contained a diverse array of cis-acting regulatory elements related to light responses, abiotic stress, phytohormones and plant growth and development. Transcriptomic analyses revealed that the expression levels of GhAG subfamily genes were lower in vegetative tissues than in flower and fruit reproductive organs. The qRT−PCR results for different tissues revealed that the GhSHP1 transcript level was highest in the cotton boll shell, and GhSHP1 was selected as the target gene after comprehensive analysis. We further investigated the functional role of GhSHP1 using virus-induced gene silencing (VIGS). Compared with those of the control plants, the flowering and boll cracking times of the GhSHP1-silenced plants were significantly delayed. Moreover, the results of paraffin sectioning at the back suture line of the cotton bolls revealed that the development of the dehiscence zone (DZ) occurred later in the GhSHP1-silenced plants than in the control plants. Furthermore, at the same developmental stage, the degree of lignification in the silenced plants was lower than that in the plants transformed with empty vector. The expression of several upland cotton genes homologous to key Arabidopsis pod cracking genes was significantly downregulated in the GhSHP1-silenced plants. These results revealed that GhSHP1 silencing delayed the flowering and cracking of cotton bolls and that the cracking of cotton bolls was delayed due to effects on DZ development. These findings are highly important for future studies of the molecular mechanism of cotton boll cracking and for breeding early-maturing and high-quality cotton varieties.